1979
DOI: 10.1111/j.1748-1716.1979.tb06468.x
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of fast axonal transport and microtubule polymerization in vitro by colchicine and colchiceine

Abstract: The effects of colchicine and colchiceine on fast axonal transport in frog sciatic nerves were studied in vitro. Colchiceine inhibited the transport to about the same extent as colchicine. Preincubation at low temperature potentiated the inhibitory effect of either drug. The polymerization of purified brain tubulin was inhibited by colchiceine at 5-10 times higher concentrations than colchicine. The similarity of the effects obtained with colchicine and colchiceine indicates that both drugs arrest axonal trans… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1984
1984
2007
2007

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 30 publications
1
3
0
Order By: Relevance
“…In order to distinguish between simple diffusion of rAAV-5 vectors from the MFB to the SNc and retrograde axonal transport, colchicine was injected into the MFB prior to rAAV-5 vector delivery. Colchicine blocks fast axonal transport by interfering with microtubule organization (14), and it has been used to inhibit retrograde transport of rAV and rAAV from the sciatic nerve to the spinal cord in mice and rats (4). In agreement with previous observations (15), the dose of colchicine applied in this study did not change the morphology of TH-positive neurons in the SNc (Fig.…”
Section: Transduction Of the Nigrostriatal Pathway After Vector Delivsupporting
confidence: 81%
“…In order to distinguish between simple diffusion of rAAV-5 vectors from the MFB to the SNc and retrograde axonal transport, colchicine was injected into the MFB prior to rAAV-5 vector delivery. Colchicine blocks fast axonal transport by interfering with microtubule organization (14), and it has been used to inhibit retrograde transport of rAV and rAAV from the sciatic nerve to the spinal cord in mice and rats (4). In agreement with previous observations (15), the dose of colchicine applied in this study did not change the morphology of TH-positive neurons in the SNc (Fig.…”
Section: Transduction Of the Nigrostriatal Pathway After Vector Delivsupporting
confidence: 81%
“…58,59 Since it binds to the colchicine-tubulin complex, it is suggested that colchicine binds at a site different from the colchicine site on tubulin. 60 Precolchicine (a colchicine-like compound with rearranged bond system; Fig. 4i) is not active.…”
Section: B Role Of the C Ringmentioning
confidence: 98%
“…On the other hand, EIN and COL differ only in substitution at the O-10 atom (-H for EIN vs.-CH 3 for COL; for structures see Figure 4). The ability of EIN to disrupt microtubules is an order of magnitude lower than that of COL (Edstrom et al, 1979;Staretz and Hastie, 1993). Therefore, the finding that EIN does not affect expression and transcriptional activities of PXR, CAR, and GR receptors favors the hypothesis of cytoskeleton-dependent GR-PXR/CAR-P450s signaling.…”
Section: Discussionmentioning
confidence: 71%